Age- and Sex-Specific Changes in Lower-Limb Muscle Power Throughout the Lifespan. (16th January 2020) - Alcazar, Julian; Aagaard, Per; Haddock, Bryan; Kamper, Rikke S; Hansen, Sofie K; Prescott, Eva; Alegre, Luis M; Frandsen, Ulrik; Suetta, Charlotte
Abstract: Background: Our main goal was to evaluate the pattern and time course of changes in relative muscle power and its constituting components throughout the life span. Methods: A total of 1, 305 subjects (729 women and 576 men; aged 20–93 years) participating in the Copenhagen Sarcopenia Study took part. Body mass index (BMI), leg lean mass assessed by dual-energy X-ray absorptiometry (DXA), and leg extension muscle power (LEP) assessed by the Nottingham power rig were recorded. Relative muscle power (normalized to body mass) and specific muscle power (normalized to leg lean mass) were calculated. Segmented regression analyses were used to identify the onset and pattern of age-related changes in the recorded variables. Results: Relative muscle power began to decline above the age of 40 in both women and men, with women showing an attenuation of the decline above 75 years. Relative muscle power decreased with age due to (i) the loss of absolute LEP after the fourth decade of life and (ii) the increase in BMI up to the age of 75 years in women and 65 years in men. The decline in absolute LEP was caused by a decline in specific LEP up to the age of 75 in women and 65 in men, above which the loss in relative leg lean mass also contributed. Conclusions: Relative power decreased (i) above 40 years by the loss in absolute power (specific power only) and the increase in body mass, and (ii) above 70 years by the loss in absolute power (both specific power and leg lean mass).